Incident infection during the first year of treatment – A comparison of clozapine and paliperidone palmitate long-acting injection. (February 2022) - Mace, Shubhra; Dzahini, Olubanke; Cornelius, Victoria; Langerman, Hadar; Oloyede, Ebenezer; Taylor, David
Background: To examine the risk of infection in patients prescribed clozapine compared with patients prescribed paliperidone palmitate long-acting injection (PPLAI). Method: A retrospective, 1-year, cohort study conducted on events occurring in eligible patients beginning treatment for the first time with clozapine or PPLAI between June 2017 and June 2019 in a UK mental health trust providing in-patient and out-patient services. Results: The study included 64 patients starting clozapine and 120 patients starting PPLAI. Incidence of infection was greater in clozapine starters than in PPLAI starters (28% vs 6%; p  = 0.001; adjusted odds ratio 5.82 (95% confidence interval (CI) = 2.15–15.76, p  = 0.001). Infectious episodes in clozapine patients were not related to changes in neutrophil counts. Incident infection in the clozapine group was highest in the first 3 months of treatment. The most commonly reported infection in the clozapine group was chest infection; however, the majority of infections were non-chest-related. Conclusion: Patients starting clozapine showed a substantially increased likelihood of infection compared with patients starting PPLAI.